HIV/AIDS em indivíduos com idade igual ou maior que 50 anos - Nunes, Djayna Serra (2013)
The increase in life expectancy, access to treating erectile dysfunction, behavioral changes in the social and sexual and non-adherence to condoms has coincided with the increasing prevalence of HIV / AIDS in the elderly. The objective of the research was to identify the socio-economic and socio-demographic and knowledge about HIV/AIDS individuals aged 50or older. Developed a descriptive transversal study through qualitative research and quantitative. The study included people aged above 50years with a confirmed diagnosis of HIV/AIDS, registered in the Service of Specialized Health, in São Luís, Maranhão, Brazil. This investigation was evaluatedin49patientsaged 50to 74 years, 77.6% were female, 91.8% in the exposure category was heterosexual,52.1% had elementary education, 89.2% had family income1-3minimum wages, 63.0% had no prior information about HIV/AIDSand91.8% were receiving antiretroviral terapy. The found data can be inferred that he study group had limited knowledge about HIV/AIDS.